2022
DOI: 10.3390/biology11050798
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Expression Analysis of Small RNA, Degradome and Microarray Reveals Complex Regulatory Action of miRNA during Prolonged Shade in Swarnaprabha Rice

Abstract: Prolonged shade during the reproductive stage can result in significant yield losses in rice. For this study, we elucidated the role of microRNAs in prolonged-shade tolerance (~20 days of shade) in a shade-tolerant rice variety, Swarnaprabha (SP), in its reproductive stage using small RNA and degradome sequencing with expression analysis using microarray and qRT-PCR. This study demonstrates that miRNA (miR) regulation for shade-tolerance predominately comprises the deactivation of the miR itself, leading to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…Through the first base bias analysis, we found that the first base of the remaining miRNAs was not U, except for miRNAs with a length of 24 nt. Whereas, in other eukaryotes, such as Drosophila, Penicillium marneffei, Swarnaprabha rice and Rat, there is a high proportion of miRNAs whose first base is U (35)(36)(37)(45)(46)(47). Considering the cutting point preference of Dicer on the first base of miRNA, this different characteristics may result in significant differences in miRNAs of E. tenella compared to other organisms (48).…”
Section: Discussionmentioning
confidence: 99%
“…Through the first base bias analysis, we found that the first base of the remaining miRNAs was not U, except for miRNAs with a length of 24 nt. Whereas, in other eukaryotes, such as Drosophila, Penicillium marneffei, Swarnaprabha rice and Rat, there is a high proportion of miRNAs whose first base is U (35)(36)(37)(45)(46)(47). Considering the cutting point preference of Dicer on the first base of miRNA, this different characteristics may result in significant differences in miRNAs of E. tenella compared to other organisms (48).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the many-fold and small increase in the level of pri-miR163 and pri-miR840, respectively, their response to high light was controlled at different steps of their biogenesis. In hyl1 mutant having disturbed pre-miRNA pro- Similarly to high light, low light intensity also modifies the expression of miRNAs, as observed in rice [140]. Shade during the reproductive stage increased the expression of miRNAs related to the cell wall, membrane, cytoskeleton, and cellulose synthesis, and it decreased the transcription of those involved in the control of photosynthesis, carbon and sugar metabolism, energy metabolism, and amino acid and protein metabolism.…”
Section: Regulatory Relationships Between the Light Intensity And The...mentioning
confidence: 83%